2016
DOI: 10.21894/jopr.2016.2804.10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Energy Utilisation in Malaysian Oil Palm Mechanisation Operation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The determination of harvesting and evacuation routes can help to impact plantation productivity, but to date, there is no meaningful research being done in this area, which is a gap that can be looked into (Lim et al, 2021). More machinery means higher energy costs and it is expected that out of the total energy needed to produce FFBs, about 2% is taken up by diesel and 10.8% by machinery (Azwan et al, 2016). It's important to carefully consider these factors when choosing an FFB evacuation method to ensure optimal results for the operation.…”
Section: Qualitymentioning
confidence: 99%
“…The determination of harvesting and evacuation routes can help to impact plantation productivity, but to date, there is no meaningful research being done in this area, which is a gap that can be looked into (Lim et al, 2021). More machinery means higher energy costs and it is expected that out of the total energy needed to produce FFBs, about 2% is taken up by diesel and 10.8% by machinery (Azwan et al, 2016). It's important to carefully consider these factors when choosing an FFB evacuation method to ensure optimal results for the operation.…”
Section: Qualitymentioning
confidence: 99%
“…Birds are sensitive to any habitat disturbance and are widely used for environmental changes indicators in biodiversity conservation evaluation studies ( Zakaria et al . 2005 ; Jambari et al . 2012 ; Alexandrino et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other studies have focussed on different oil palm production systems and indicated that biodiversity levels are higher in smallholdings than large-scale plantations (Azhar et al 2014;Syafiq et al 2016;Razak et al 2020). Oil palm agroecosystems biodiversity levels are affected by habitat quality which is related to a range of factors such as structural complexity, heterogeneity of vegetation cover, availability of food resources, alteration of microclimate and the human activities that lead to changes to the soil physical and chemical properties (Mariau 2001;Koh et al 2009;Turner & Foster 2006;Foster et al 2011;Jambari et al 2012;Azhar et al 2013;Drescher et al 2016;Meijide et al 2018). These findings showed that the negative impact of oil palm development on biodiversity could partly be mitigated by integrating the oil palm landscape with nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation